The Influence of Grit and Peer Social Support on Self-Regulated Learning and Academic Procrastination among Eleventh Grade Students at SMK Negeri 44 Jakarta - Disti Nur Kholifah; Dita Puruwita; Rizka Zakiah (The Future of Education Journal, 2026)
This study examines the effect of grit and peer social support on self-regulated learning and academic procrastination among eleventh grade students at a public vocational high school (SMK) in Jakarta. The study responds to the persistence of academic procrastination and low self-regulated learning among vocational students, presumed to stem from an internal factor (grit) and an external factor (peer social support). A quantitative, causal-associative approach was used through path analysis based on Structural Equation Modeling Partial Least Square (SEMPLS), processed with SmartPLS. The population comprised 210 eleventh-grade students, with a sample of 136 respondents drawn through proportionate stratified random sampling based on the Krejcie and Morgan table. The results show that grit positively and significantly affects self-regulated learning (β = 0.201; p = 0.002), peer social support positively and significantly affects self-regulated learning (β = 0.612; p = 0.000), grit negatively and significantly affects academic procrastination (β = -0.398; p = 0.000), peer social support negatively and significantly affects academic procrastination (β = -0.237; p = 0.009), and self-regulated learning negatively and significantly affects academic procrastination (β = -0.287; p = 0.001). These findings suggest that strengthening grit and cultivating supportive peer relationships can enhance self-regulated learning while reducing academic procrastination, offering practical implications for character based and peer support oriented learning strategies in vocational education.